AN ANALYSIS OF THE PLURALITY OF POLITICAL ISLAM. THE CASES OF TUNISIA, TURKEY AND MOROCCO: THE CASES OF TUNISIA, TURKEY AND MOROCCO - Labrado Calera, Elena María (Journal of the Spanish Institute for Strategic Studies, 2018)
In this paper, we will analyse Political Islam based on three cases in verydifferent geographical locations, at varying stages of development andwhich have sought different solutions to problems and challenges. Allwith the aim of demonstrating, as the title suggests, the plurality or, ifyou like, the complexity or diversity of a political movement that is farfrom monolithic.
Keywords: Morocco; Tunisia; Turkey; Islam